Capital humano y señalización: evidencia para el área metropolitana de Cali, 1988-2000 - Castellar, Carlos; Uribe, José (Sociedad y Economía, 2004)
The paper contrasts and discusses two theoretical approaches (human capital and signaling, the latter in its sheepskin version) used in the evaluation of the impact of education as an asset within the labor market. Fundaments are reviewed, a methodological proposal is made in order to bring empirical evidence to the debate (using data from the metro politan area of Cali) and, finally, some conclusions nd implications for economic policy are drawn.